منهج الإمام الشافعي في إثبات حجية حديث الآحاد في كتابه الرسالة: (دراسة تحليلية) - Anwar, Saepul; Kusnadi (Indra Institute Research & Publication, 2024)
This research sets out to study the methodology of Imam Shafi'i as presented within his book